HUBUNGAN ANTARA KARAKTERISTIK DOSEN DAN KESEJAHTERAAN, SERTA IMPLIKASINYA DALAM MANAJEMEN PENDIDIKAN ISLAM: PEBI JULIANTO - JULIANTO, S.Sos., MM., CHt, PEBI (LPPM STIA Nusantara Sakti, 2024)
Faculty welfare in the context of Islamic education is heavily influenced by their job characteristics, such as task variety, level of autonomy, and feedback received (Amalia, 2020). The phenomenon of presenteeism, where despite being physically present at work, productivity declines, poses a significant challenge in academic environments (Amalia, 2020). The Islamic education management approach offers a framework based on principles like justice and accountability, which are crucial for supporting faculty welfare. This study utilized a literature review to explore the relationship between faculty characteristics and their welfare in the context of Islamic education. Key findings indicate that job satisfaction can mediate the relationship between job design factors, such as task variety and autonomy, and the level of presenteeism among faculty members (Amalia, 2020). The implications of this research include the application of job design taxonomy in Islamic education, which can enhance understanding of the linkage between job characteristics and faculty welfare. The study also highlights the importance of integrating spiritual values, personality traits, and social networks in developing holistic educational strategies in Islamic institutions, thereby fostering inclusive and empowered educational communities.